CCDC154 Mutant Caused Abnormal Remodeling of the Otic Capsule and Hearing Loss in Mice - Xu, Kai; Bai, Xue; Chen, Sen; Xie, Le; Qiu, Yue; Li, He; Sun, Yu (Frontiers in Cell and Developmental Biology, 2021)
Osteopetrosis is a rare inherited bone disease characterized by dysfunction of osteoclasts, causing impaired bone resorption and remodeling, which ultimately leads to increased bone mass and density. Hearing loss is one of the most common complications of osteopetrosis. However, the etiology and pathogenesis of auditory damage still need to be explored. In this study, we found that a spontaneous mutation of coiled-coil domain-containing 154 (CCDC154) gene, a new osteopetrosis-related gene, induced congenital deafness in mice. Homozygous mutant mice showed moderate to severe hearing loss, while heterozygous or wild-type (WT) littermates displayed normal hearing. Pathological observation showed that abnormal bony remodeling of the otic capsule, characterized by increased vascularization and multiple cavitary lesions, was found in homozygous mutant mice. Normal structure of the organ of Corti and no substantial hair cell or spiral ganglion neuron loss was observed in homozygous mutant mice. Our results indicate that mutation of the osteopetrosis-related gene CCDC154 can induce syndromic hereditary deafness in mice. Bony remodeling disorders of the auditory ossicles and otic capsule are involved in the hearing loss caused by CDCC154 mutation.